Measuring risk-taking and patience in financial decision making - Wolfgang Breuer; Thomas Renerken; Astrid Juliane Salzmann (Review of Financial Economics, 2021)
We empirically compared the consistency among different kinds of measures for risk-taking and patience in a survey and an experiment. We evaluated how these variables relate to financial decisions, using a novel set of easy-to-apply survey questions as proxy. The main finding is that our results based on the novel survey questions describing financial behavior and on lifelike financial behavior in the laboratory are very similar. Therefore, relatively low-cost elicitation measures may be used to forecast decision making, which, in turn, may be described by our novel set of survey questions.
Keywords: 330; decision making; preferences; risk attitude; time preferences